Proletários das secas: arranjos e desarranjos nas fronteiras do trabalho (1877-1919) - Cândido, Tyrone Apollo Pontes (2014)
The new experiences that developed during the droughts of the late nineteenth century included the recruitment of thousands of refugees (men, women and children) to work in construction works (railroads, highways, dams, urban buildings, pavements etc.) Recruitment grew as a measure of social control and was a condition for the groups of [flagellates—to have access to government aid. This thesis seeks to show how these migrants, dealing with different dimensions of experience that filled the day to day work and migration in drought years, were agents of their own development as a specific formation of workers, becoming in this way the drought’s proletarians. To this end, I seek to examine the various arrangements and changes that produced their forms of resistance on their journeys and in their daily work, and, from another point of view, the corresponding forms of arrangements and changes of the mechanisms of social control by the agents of power over this group of workers.